Reaching out across lines: Determinants of positive intergroup interaction in conflict-affected communities in Myanmar. Issue 2 (3rd July 2021) - van Zaal, Karen; O'Brien, MaryRose; Guyer, Patrick
ABSTRACT: In Myanmar, progress toward achieving the SustainableDevelopment Goals is severely constrained by protracted conflictand widespread internal displacement. This article exploresthe determinants of contact between people who are internallydisplaced and those who are not, as well as participation incommunity-level peacebuilding initiatives, among people livingin conflict affected communities in Kachin and northern Shanstates. We root our work in a discussion of the current andhistorical context of the conflict in Myanmar in which tensionsbetween different displacement groups are long lasting, aprogram contributing to peace, security, stability, and sustainabledevelopment in Myanmar, and a brief review of contact theory.Research for this piece was completed prior to the military coupin Myanmar in February 2021. Although the analysis does notreflect the coup or its after-effects, the findings are still relevant fordevelopment, humanitarian relief, and peacebuilding projects.